Energy Recovery in SWRO Desalination: Current Status and New Possibilities - Schunke, Andrew James; Hernandez Herrera, German Alberto; Padhye, Lokesh; Berry, Terri-Ann (Frontiers in Sustainable Cities, 2020)
Reverse osmosis (RO) technology requires high energy input in order to extract freshwater from seawater. Improvements in RO technology have led to seawater RO (SWRO) becoming the dominant form of large scale desalination around the world. However, the specific energy consumption (SEC) of SWRO remains substantially higher than that for surface water treatment and indirect potable recycling, making SWRO less cost effective than other alternatives for producing potable water. Furthermore, where non-renewable energy sources are used to supply SWRO energy demand, higher levels of greenhouse gas are emitted compared with lower energy alternatives. The purpose of this paper is to review the RO process configurations currently available and their impact on reducing SWRO energy consumption. This paper highlights the main factors contributing to SWRO energy consumption and presents some of the commonly adopted approaches to reducing SEC in SWRO plants. The use of energy recovery devices (ERDs) in SWRO is explored and the relative effectiveness of the various types of ERDs in reducing SEC presented.